Near Toco, Trinidad B.W.I. - (:unkn) unknown (Pereira and Co. Ltd., Trinidad, 2009)
Coastal view of the north-east coast of Trinidad near Toco.
Color: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Beaches--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Toco